2000
DOI: 10.1007/s11920-000-0036-0
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety disorders in the elderly

Abstract: Although the epidemiology, neurobiology, and treatment of anxiety disorders have received considerable attention in the child and adult literature, they have not received the same consideration in the geriatric population. This disparity is remarkable given the prevalence and associated costs of these disorders that can persist into late life. Further, although a considerable amount is known about these disorders in younger age groups, it is unclear whether the phenomenology of anxiety evolves over the course … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 48 publications
1
11
0
Order By: Relevance
“…Our sample of PD patients showed a high prevalence of DSM‐IV anxiety disorders (28%), and high rates of comorbid depressive illness (17%) compared with the prevalence rates observed in the general non‐PD older participants (10%) [16–18]. Panic disorder, social phobia and generalized anxiety disorder predominated and this was similar to previous reporting of anxiety disorders found in PD patients [19–21].…”
Section: Discussionsupporting
confidence: 85%
“…Our sample of PD patients showed a high prevalence of DSM‐IV anxiety disorders (28%), and high rates of comorbid depressive illness (17%) compared with the prevalence rates observed in the general non‐PD older participants (10%) [16–18]. Panic disorder, social phobia and generalized anxiety disorder predominated and this was similar to previous reporting of anxiety disorders found in PD patients [19–21].…”
Section: Discussionsupporting
confidence: 85%
“…In our case series of PD subjects, 25% fulfilled the criteria for a current anxiety disorder. This was much higher than the prevalence reported in epidemiological studies focussing on non‐PD subjects in Australia and elsewhere 26–28. These previous studies have reported an average anxiety prevalence of 10% in the general elderly community.…”
Section: Discussionmentioning
confidence: 58%
“…Anxiety is also common in PD . Clinically significant anxiety has been reported as ranging between 5% and 60% in patients with PD, a prevalence markedly greater than the rate of 10% in the general population and older adults . All types of anxiety disorders have been reported in PD, but generalized anxiety disorder (GAD), panic disorder, and social phobia appear most common .…”
Section: Prevalence and Impact Of Anxiety And Depression In Pdmentioning
confidence: 99%
“…10 Clinically significant anxiety has been reported as ranging between 5% and 60% in patients with PD, 11 a prevalence markedly greater than the rate of 10% in the general population and older adults. [12][13][14][15] All types of anxiety disorders have been reported in PD, but generalized anxiety disorder (GAD), panic disorder, and social phobia appear most common. 3,10 GAD is characterized by excessive and uncontrollable worry accompanied by physiological arousal; eg, muscle tension.…”
Section: Prevalence and Impact Of Anxiety And Depression In Pdmentioning
confidence: 99%